PjBL Model assisted by Smartphone Sensors to Improve Critical Thinking Skills of Prospective Science Teachers - Prasetyo Listiaji; Risti Ayu Widianingrum; Anggita Ayu Ivanda Saputri; Nor Farahwahidah Abdul Rahman (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2022)
This research aims to analyze the improvement of the critical thinking skills of prospective science teachers after the implementation of smartphone-assisted PjBL and analyze the responses of prospective science tea-chers to the applied learning model. The research used an experimental model with a Nonequivalent Control Group Design. The research subjects were 2nd semester Science Education Program students in 2 classes of basic physics courses (experimental and control) as prospective science teachers. Data collection methods were test techniques for measuring critical thinking skills and questionnaire methods for determining stu-dent responses. Data analysis methods ware N-Gain analysis, independent sample t-test, and qualitative descriptive. The results showed a high increase in critical thinking skills in the experimental class, as indi-cated by an N-Gain score of 0.71. The results of the hypothesis test also showed that there was a significant difference between the post-test scores of the experimental and control classes. The PjBL model assisted by smartphone sensors also received a very good response from prospective science teacher students. The PjBL model assisted by smartphone sensors can be implemented to improve the critical thinking skills of pros-pective science teachers and can also be a reference for innovative learning models that align with the de-mands of technology-based 21st-century learning.